Robust channel estimation for OFDM wireless communication systems - an H∞ approach. - Jun Cai
In this paper, the joint time-frequency domain channel estimation problem in orthogonal frequency-division multiplexing (OFDM) wireless communication systems is transformed to a set of independent time-domain estimation problems. A robust channel estimation algorithm based on the H∞ filtering approach is proposed to estimate the channel fading in the time domain. The estimation criterion is to minimize the worst possible amplification of the estimation errors in terms of the exogenous input disturbances such as multiplicative and additive noise. The criterion is different from the traditional minimum estimation error variance criterion for the Kalman estimation algorithm, and requires no a priori knowledge of the disturbance statistics. It is shown that the proposed channel estimation algorithm is more robust compared with the Kalman estimation counterpart in terms of model uncertainty, and is more suitable to practical OFDM wireless communication systems.
Keywords: Kalman estimation algorithm; OFDM wireless communication system; Additive noise; Channel fading; Disturbance statistics; Exogenous input disturbance; Joint time-frequency domain; Minimum estimation error variance criterion; Multiplicative noise; Orthogonal frequency-division multiplexing; Robust channel estimation algorithm; Time-domain estimation; H∞ filtering